Reducing Anemia Among School-Aged Children in China by Eliminating the Geographic Disparity and Ameliorating Stunting: Evidence From a National Survey - Wang, Jun-Yi; Hu, Pei-Jin; Luo, Dong-Mei; Dong, Bin; Ma, Yinghua; Dai, Jie; Song, Yi; Ma, Jun; Lau, Patrick W. C. (Frontiers in Pediatrics, 2020)
Background: To assess the geographic disparity in anemia and whether stunting was associated with anemia in different geographic groups among school-aged children in China. Methods: 71,129 Han children aged 7, 9, 12 and 14 years old were extracted from the 2014 cycle of Chinese National Surveys on Children Constitution and Health. Anemia, anemia severity and stunting were defined according to WHO definitions. Binary logistic regression models were used to estimate the association between anemia and stunting in different geographic groups. Results: The prevalence of anemia was obviously higher in girls (10.8%) than boys (7.0%). The highest anemia prevalence was in Group VII (lower class/rural, 12.0 %). The moderate/severe prevalence of anemia was concentrated in Group VII and Group VIII (western/lower class/rural) for both sexes. The prevalence of anemia was higher in stunting boys than non-stunting boys in Group IV (lower class/city, 𝒳2=12.78, P=0.002) and Group VII (𝒳2=6.21, P=0.018), while for girls, it was higher in stunting girls than their non-stunting peers only in Group II (upper class/large city, 𝒳2=4.57, P=0.046). Logistic regression showed that the stunting children have 30% higher risk of anemia than non-stunting children after adjustment for age, sex and school (OR=1.30, 95%CI: 1.05-1.60). Conclusion: A significant geographic disparity and an association between anemia and stunting among specific groups of school-aged children in China were demonstrated. Consequently, eliminating the geographic disparity and ameliorating stunting might contribute to the improvement of Chinese children’s anemia. Specific guidelines and interventions are needed, especially for adolescent girls and the groups with serious anemia burden.